TRADITIONAL GRAMMAR IN THE ERA OF INDEPENDENT LEARNING - I Nyoman Adi Susrawan (Jurnal Cakrawala Ilmiah, 2022)
Grammar is a very important reference in the language learning process, but it is also an obstacle and a challenge for the teacher. This study aims at knowing the use and relevance of Traditional Grammar in the era of independent learning. This study made use of library research to collect the required data. The results of the study showed that Traditional Grammar is still relevant to be used in language learning in this era of independent learning, of course by providing modifications in its application. This study reveals the importance of Traditional Grammar in the era of independent learning.